Design Secured Smart Door Lock Based on Jaro Winkler Algorithm - Sura Mahmood Abdullah (Tikrit Journal of Pure Science)
The security nowadays considered as significant topic specifically in design smart home. This paper is dedicated on an authentication problem in design smart door lock authentication using string matching technique based on password string.